A Global Perspective on Vaccines: Priorities, Challenges and Online Information - Leite, Luciana; Tagliabue, Aldo; Rappuoli, Rino; Yvonne Leroy, Odile; Leite, Luciana; Tagliabue, Aldo; Rappuoli, Rino; Yvonne Leroy, Odile (Frontiers Media SA, 2020)
Vaccines have been one of the most important medical discoveries of the last three centuries. Thanks to their development, millions of deaths have been avoided. Together with improved hygiene and antibiotics, vaccines have significantly contributed to the prolongation of life expectancy in high-income countries to a current average of 85 years, compared to 47 years in 1900. However, the continued success of vaccination has recently been hampered due to changes in the perception of vaccines within society. Therefore, there is a critical need to better understand (i) what has been achieved by vaccination thus far and (ii) what is important to further develop vaccines in a world where increased population, aging, travel, urbanization and climate change favor the emergence, evolution and spread of old and new pathogens. In this Research Topic, we gather articles that discuss numerous questions and problems associated with vaccines. The future of vaccine development needs to take in account changing perspectives within our society and that the acceptance of preventative medicine may also change in the years to come.
Keywords: Medicine; Immunology; vaccines; antimicrobial resistance; vaccine hesitancy; vaccine education; technological platforms